The relationship between organisational culture and knowledge management culture. (23rd January 2020) - Chang, Christina Ling-hsing; Lin, Tung-ching
This study expect to explore the relationship between organisational culture, knowledge management (KM) culture, and an individual's KM intention in the KM process, and to clarify the relationship between the eight dimensions of organisational culture and KM culture, in order to understand the effect of KM culture on an individual's KM intention in the KM process. The contribution of this study for management is the insight, that to facilitate the KM culture in their organisation, they should encourage results-oriented, solidarity, sociability, and strong cultures, and discourage a job-oriented culture. At the same time, encouraging a strong culture and a KM culture will increase the employees' intention to directly manage their knowledge in the KM process; but plays a significantly negative moderate role between the KM cultures and an individual's KM intention.